Wpływ żywicowania na przyrost radialny sosny zwyczajnej (Pinus sylvestris L.) na przykładzie drzewostanu w Nadleśnictwie Lidzbark - Magnuszewski, Michał; Tomusiak, Robert (Leśne Prace Badawcze, 2013)
The study makes an attempt to evaluate the effect of resin-tapping on the radial increment of Scots pine ( Pinus sylvestris L.). Increment cores were taken from two groups of trees: resin-tapped trees and normal trees growing in a 148–year-old pine stand in the Lidzbark Forest District. The cores were taken with the Pressler increment borer from two heights on the tree trunk: 1.30 m and 3.30 m. Using dendrochronological methods, real chronologies were built for each of the four analysed groups of cores. The value and variability of increments for each group were investigated in 20 and 40 year time periods, before and after the start of resin-tapping. In next step, the chronologies were compared and their coefficients of conformity were calculated. As a result, we can state that the radial increments were larger are at 1.3 m height after resin-tapping than before resin-tapping. There was also significant effect of resin-tapping on radial growth at the height 3.3 m, above the resin-tapping face.